2000
DOI: 10.1021/jp9932261
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Mechanism of the Activation of ClONO2by HCl in Small Water Clusters Using Electronic Structure Methods

Abstract: High-level electronic structure calculations were used to study the mechanism of the reaction of ClONO 2 with HCl in neutral water clusters containing one to five solvating water molecules. For the reaction between molecular HCl and ClONO 2 , the barrier decreases from 42 kcal mol -1 (uncatalyzed) to essentially zero when catalyzed by only two water molecules, where the reaction products involve Cl 2 and HONO 2 . The calculations thus predict that the gas-phase reaction may be important in the stratospheric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 92 publications
3
29
0
Order By: Relevance
“…In the following discussions, for all hydration numbers of clusters n = 1, 2, and 3, the same letters are used for molecular labels for products (A, B), for optimized structures (C, D, E, ...) in increasing order of the relative energy, and for TSs the asterisk is added to these letters for the sake of convenience. Two isomeric structures are found as reactants in n = 0 cluster (Figure 1), where isomer 0D was previously found by McNamara et al 7 Although 0D was reported to be the reactant with the hydrogen bond between two atoms O5 and H7, the new reactant isomer 0C is found to be more stable than 0D with a hydrogen bond between O2 and H7. In 0C, HCl molecule coordinates to ClONO 2 in the direction perpendicular to the molecular plane of ClONO 2 .…”
Section: Stable and Ts Structures For Clonosupporting
confidence: 65%
See 1 more Smart Citation
“…In the following discussions, for all hydration numbers of clusters n = 1, 2, and 3, the same letters are used for molecular labels for products (A, B), for optimized structures (C, D, E, ...) in increasing order of the relative energy, and for TSs the asterisk is added to these letters for the sake of convenience. Two isomeric structures are found as reactants in n = 0 cluster (Figure 1), where isomer 0D was previously found by McNamara et al 7 Although 0D was reported to be the reactant with the hydrogen bond between two atoms O5 and H7, the new reactant isomer 0C is found to be more stable than 0D with a hydrogen bond between O2 and H7. In 0C, HCl molecule coordinates to ClONO 2 in the direction perpendicular to the molecular plane of ClONO 2 .…”
Section: Stable and Ts Structures For Clonosupporting
confidence: 65%
“…McNamara et al 7 elucidated the reaction mechanisms for n ≤ 3 clusters and few structures with n = 4 and 5 using ab initio molecular orbital (MO) calculations by the second-order Møller−Plesset (MP2) perturbation theory for optimized structures obtained by Kohn−Sham density functional theory with a combination of Becke's three-parameter exchange and Lee−Yang−Parr correlation functional (B3LYP) with the 6-311++G(d,p) basis set. They showed that the reaction barriers were lowered systematically by adding water molecules to the complex.…”
Section: Introductionmentioning
confidence: 99%
“…greatly improved our detailed understanding of heterogeneous reactions involving HCl on ice surfaces. 35,36 The studies of HBr on ice are less numerous than those in the case of HCl. In fact, a phase diagram of the HBr/ice system has not yet been constructed for low temperatures even though an ionic trihydrate of HBr reportedly has been found.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the ice surface reaction would involve where H 3 O`Clã n initial step may involve the desolvation of Cl~and thus contribute to increasing the barrier somewhat. 39,43,44 The increased availability of water on the ice surface (compared to the gas phase) may also lead to the Ðnal reaction products involving ionised nitric acid However, Sodeau O`Cl~) whereby developing charged species is stabilised by additional waters. This has been shown to be the case for reactions (2), (4) and (5).…”
Section: Discussionmentioning
confidence: 99%